2005
DOI: 10.1007/s00213-005-2261-z
|View full text |Cite
|
Sign up to set email alerts
|

5-HT6 receptor antagonists improve performance in an attentional set shifting task in rats

Abstract: 5-HT(6) receptor antagonists improved performance in the attentional set shifting task and may have therapeutic potential in the treatment of disorders where cognitive deficits are a feature, including schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(72 citation statements)
references
References 38 publications
(48 reference statements)
1
71
0
Order By: Relevance
“…In both vehicle and PCP-treated rats the first reversal (R1) required more trials to reach criterion compared to earlier stages of the task. This is supported by data showing a significant increase in trials to criterion in control rats [26]; however, other studies have shown more modest increases [8,16,18].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In both vehicle and PCP-treated rats the first reversal (R1) required more trials to reach criterion compared to earlier stages of the task. This is supported by data showing a significant increase in trials to criterion in control rats [26]; however, other studies have shown more modest increases [8,16,18].…”
Section: Discussionmentioning
confidence: 57%
“…Clozapine has affinity at a wide range of receptors including 5-HT 6 receptors. A selective 5-HT 6 receptor antagonist has been shown to improve set-shifting ability [26], this may be via facilitation of cortical and hippocampal glutamatergic activity [12].…”
Section: Discussionmentioning
confidence: 99%
“…Activity at 5-HT 6 receptors has been postulated to be important in cognitive dysfunction (Mitchell and Neumaier, 2005) and psychopathology (East et al, 2002), and in the present study, the 5-HT 6 antagonist reversed the PCP-induced impairment as did sertindole, while the 5-HT 2A receptor antagonist treatment did not improve EDS performance significantly, very similar to effects observed with clozapine, olanzapine, and risperidone. Although a previous study reported that receptor antagonist treatment improved performance in control rats (Hatcher et al, 2005), a more recent study found that selective 5-HT 6 receptor antagonism reversed PCP deficits without influencing performance in control rats (Wunsch et al, 2006). These latter findings are consistent with those of the current study.…”
Section: Discussionmentioning
confidence: 98%
“…Drugs were administered immediately before behavioral testing, with the exception of sertindole (2 h, due to a delayed peak effect), to evaluate the effects of drug on all discrimination problems in the set-shifting procedure. We selected dose ranges for compounds that did not produce behavioral disruption and that have been shown to induce DA D 2 receptor occupancies corresponding to therapeutically effective levels (Olsen et al, 2006) or to be effective in relevant mechanistic in vivo models (Zhang and Bymaster, 1999;Sanchez and Arnt, 2000;Hatcher et al, 2005;Wunsch et al, 2006). The compounds examined differ on activity at DA D 2 , 5-HT 2A , and 5-HT 6 receptors.…”
Section: Drug Administrationmentioning
confidence: 99%
“…5-HT 6 R antagonists also enhanced acquisition and reversed a scopolamine-evoked deficit in rat operant autoshaping and passive avoidance tasks (Bos et al, 2001;Meneses, 2001;Riemer et al, 2003). Pretreatment with a 5-HT 6 R antagonist also improved rat performance of an attentional set-shifting task, a rodent analog of the Wisconsin card sorting test, a commonly used assay of cognitive-guided sorting (Hatcher et al, 2005). However, other investigators have been unable to demonstrate 5-HT 6 R-induced enhancements of cognitive function (Russell and Dias, 2002;Lindner et al, 2003).…”
Section: -Ht 6 R-influenced Behaviorsmentioning
confidence: 99%